A feminist examination of the position of African women in selected female African novels - Makgwale, Monthabeng Hassel (My University, 2022)
This study will examine the position of traditional African women as explored in the fictions, The Joys of Motherhood (Buchi Emecheta) and So Long a Letter (Mariama Bâ). It will probe into the depiction of a traditional African woman in the selected texts under thematic issues which will assist us in understanding how Emacheta and Ba perceive issues that directly impact the lives of women, even today. The issues include patriarchy, marriage, motherhood and childbearing, sex and gender, objectification of women, and the role of the chief wife. Both Emecheta and Bâ use communal voices that blend cultural incidents with fiction to demonstrate the subordinate role played by women in traditional African societies that are characterised by patriarchal practices and suppression of women. Both Emecheta and Bȃ demonstrate cultural and religious stereotypes towards African women. This study will apply the African womanism lens as a theoretical framework to underpin it. The study will attempt to reveal that, from the selected texts, contemporary African women writers oppose the injustice inflicted upon them through marriage or gender (sex) stereotypes. The selected fictions help the audience understand the plight of some African women.
Thesis (M.A. (English Studies)) -- University of Limpopo, 2022
Keywords: Feminism; Patriarchy; Marriage; Motherhood; Sex and gender; Objectives of women; Chief wife; Widowhood; Feminism -- Africa; Sex discrimination; Marriage; Patriarchy; English fiction -- History and criticism; Feminism and literature